An Efficient Public Auditing Protocol With Novel Dynamic Structure for Cloud Data - Jian Shen; Jun Shen; Xiaofeng Chen; Xinyi Huang; Susilo, Willy (IEEE transactions on information forensics and security, 2017)
With the rapid development of cloud computing, cloud storage has been accepted by an increasing number of organizations and individuals, therein serving as a convenient and on-demand outsourcing application. However, upon losing local control of data, it becomes an urgent need for users to verify whether cloud service providers have stored their data securely. Hence, many researchers have devoted themselves to the design of auditing protocols directed at outsourced data. In this paper, we propose an efficient public auditing protocol with global and sampling blockless verification as well as batch auditing, where data dynamics are substantially more efficiently supported than is the case with the state of the art. Note that, the novel dynamic structure in our protocol consists of a doubly linked info table and a location array. Moreover, with such a structure, computational and communication overheads can be reduced substantially. Security analysis indicates that our protocol can achieve the desired properties. Moreover, numerical analysis and real-world experimental results demonstrate that the proposed protocol achieves a given efficiency in practice.